Pleito quilombola e conflito territorial em Minas Gerais: o "caso" do Boqueirão versus PCH Mucuri - Lara Cyreno de Carvalho Lima (2009)
This work has as central objetive to bring contributions to the studies over the Quilombola theme, considering that the Quilombolas present themselves as political subjects ethnically marked, takimg part in the scenario of territorial conflicts. Supported by the law, they started out on the search for the guarantee over their lands within the Marques Quilombola community, it was observed how the group stands in the face of the impact generated by the project of construction of a small Hydroelectrical Central . In front of these circumstances, some of the families of the Marques community motivated themselves collectively, starting out a territorial claiming, as they publically stated their Quilombola identity, which raised both internal e external conflicts around the group.